“Time is brain”- management of the patient with iatrogenic intracerebral hemorrhage (Indian Journal of Case Reports, 2018)
The brain is a critical organ of our body, which depends on a continuous supply of oxygen and glucose for normal functioning. An inadequate supply of oxygen and glucose can trigger a characteristic pathophysiological cascade leading to neuronal death. Multiple neuroprotective strategies have been developed blocking one or more steps along this cascade. Here, we report the case of an intracerebral hemorrhage during neurointerventional procedure in a catheterization laboratory. Accurate decision and timely intervention of neuroprotective strategies resulted in the complete neurological recovery of the patient.